Pelayanan UPT Puskesmas Batang Kulur Kecamatan Sungai Raya Kabupaten Hulu Sungai Selatan - Agus Sya’bani Arlan (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
The research methods  used are qualitative methods,  data  collection techniques, namely: observation, interviews and documentation.  The data source was taken through  informants totaling 15 people, using  data  analysis techniques, namely through   the stages of reduction, data presentation and drawing conclusions, while  the test  Data credibility using triangulation.The results showed that the  service at the UPT Puskesmas Batang Kulur, Sungai  Raya  District,  Hulu Sungai Selatan Regency, was quite good.  Of the 10 subvariables,  there are 2 good things,  namely: komitmen from management and pengetahu management about quality.  Subvariables that show  quite good results are found in:  the ability to change culture, the ability to build a leadership organization, the value of rewarding and rewarding employees and  the  conformity between structures. organization.  Subvariables that show poor results   are found in: sustainablecycling, planning accuracy  , adequacy of resources and funds and accuracyof adopting quality management principles into the organization.  The factors thathinder the p elayanan  di UPT Puskesmas Batang Kulur, Sungai Raya District, Hulu Sungai Selatan Regency, p ertama, lack of discipline of time of Puskesmas officers in providing services to the community, k edua, k urangnya puskesmas employees in providing services to the community,  k etiga, weinclude employees in the sustainable cycling.  The efforts made to address these  inhibiting factors are: pertama, it is hoped that puskesmas officers  in providing services to the community so that they can   on time, kedua,  adding Puskesmas officers in  providing services  to patients / the community so that the services provided by UPT Puskesmas officers can run well,   third, include officers   in training   sustainable.To improve services at  UPT Puskesmas Batang  Kulur, Sungai  Raya  District,  Hulu Sungai Selatan Regency, it is recommended to the Head of  UPT  Puskesmas Batang Kulur to  convey to  the Head of the Health Office   to  add service officers at   UPT Puskesmas so that services at puskesmas  can run well  and in accordance with the service process.  Meanwhile, Puskesmas employees  are expected to  improve discipline at  work and continue  to  motivate themselves to support the  smooth process of  services provided at the  Batang   Kulur Health Center.  Sungai  Raya  Subdistrict, Hulu Sungai Selatan Regency. For sustainable training  programs, it is hoped that the Head of UPT  Puskesmas Batang Kulur will provide opportunities for their employees. As for the  community, they  are encouraged to participate  in the smooth service process  at the  Batang Kulur Health Center. Keywords: Quality of Service; Public Health; Batang Kulur Health Center